Throwing the Spanner in the Works: The Mixed Blessing of FDI - Jakob Schwab (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
I incorporate imperfect capital markets in a standard neoclassical model of economic growth to analyze the long run effect of capital market globalization for develping countries. In autarky, domestic savings are invested and Solow-type growth emerges. In contrast, when a country that lags behind in the growth process opens up to international capital markets, FDI flows in. This lowers returns to investment and thus the possibility of domestic agents to build up capital. Although short term benefits in terms of increased wage rates occur, the wedge between the returns to investment and savings that is constantly reaped by foreign investors is foregone for domestic agents in the long run and - compared to the autarky case - national income is lower.
Keywords: F21; F43; O16; 330